IMPLEMENTATION OF E-HRM IN IMPROVING EFFICIENCY AND EMPLOYEE WELFARE IN THE SOCIETY 5.0 ERA - Azwar Maulana; M. Fikri Darussalam; Khuzaini; Syahrial Shaddiq (PT. Hasba Edukasi Mandiri, 2025)
The digital transformation of Human Resource Management (HRM) has driven the adoption of electronic Human Resource Management (e-HRM) systems to enhance organizational efficiency. However, an efficiency-centered approach may overlook employee well-being. Within the Society 5.0 framework, technology is expected to empower humans, not merely control them. This study aims to analyze how e-HRM can be implemented in an integrative way to support both efficiency and employee well-being. A conceptual-qualitative approach was employed through a literature review of 22 accredited academic sources published between 2015 and 2025. The findings reveal that effective e-HRM lies in the balance between administrative automation and humanistic features such as employee feedback systems, personalized learning platforms, and well-being monitoring tools. This study proposes a conceptual model of e-HRM grounded in the values of Society 5.0, placing human welfare as a central indicator of sustainable efficiency. The results are expected to serve as a reference for HR practitioners and organizational policymakers in developing adaptive and human-centered digital work systems..